Inflammatory immune reactivity to cereal proteins in type 1 diabetes - Lefebvre, David E (University of Ottawa (Canada), 2007)
Background. Type 1 diabetes (T1D) is an autoimmune disease in which a patient's immune system destroys the insulin-secreting beta-cells in the pancreas. The origin of beta-cell-specific leukocytes and the identity of the stimulatory antigens remain unknown. Disease development in individuals with genetic risk is thought to require environmental triggers. Epidemiological data and evidence from animal models suggests that exposure to dietary wheat can enhance diabetes autoimmunity. Some evidence suggests a crucial role of the gut barrier and gut-associated lymphoid tissues (GALT). Hypothesis . The gut in T1D susceptible rodents and patients is dysfunctional and characterized by a pro-inflammatory immune microenvironment which is associated with a loss of tolerance to cereal proteins. Methods. The inflammatory status of the GALT of diabetes-prone BioBreeding (BBdp) rats was quantified by RT-PCR, ELISA, and immunoblotting for T helper 1/T helper 2 (Th1/Th2) cytokine markers. T cell reactivity to wheat proteins was quantified by flow cytometric proliferation assay with cells from the GALT of BBdp rats and with peripheral blood mononuclear cells (PBMCs) from patients with type 1 diabetes. The effect of microbes and diet on diabetes outcome was characterized by feeding trials in germ-free BBdp rats. Results. T-bet/GATA-3 transcription factor expression ratio reflected Th1/Th2 immune cell status in the BB rat and provided a snapshot of the in vivo inflammatory status of tissues. At an age which pre-dates the development of T 1D, the GALT of BBdp rats, fed a diabetes-promoting cereal-based diet, contained an unusually high proportion of pro-inflammatory Th1 cells. These T cells specifically responded to wheat proteins in vitro. Similarly, T cell reactivity to wheat proteins was also observed in PBMCs in a subset of patients with T1D. PBMCs from a patient with T1D and celiac disease-associated gut damage revealed strong Th1-biased immune reactivity to wheat protein. Diabetes was promoted by a cereal-based diet in both the presence and absence of microbes in BBdp rats, and a diabetes-promoting effect of microbes was revealed in the absence of cereal proteins. Conclusions. At ages which precede diabetes, a pro-inflammatory state in the gut and GALT of BBdp rats is associated with the activation of wheat-specific T cells. An immune response to wheat is also present in PBMCs in a subset of patients with T1D. A low-antigen diet inhibited the development of diabetes in BBdp rats and almost completely prevented diabetes in germ-free BBdp rats. These findings suggest that the gut could play an important role in the development of T1D.
Keywords: Chemistry, Biochemistry.